Black queen cell virus detected in Canadian mosquitoes. Issue 2 (2nd April 2023) - Baril, Cole; LeMoine, Christophe M R; Cassone, Bryan J
Abstract: Black queen cell virus (BQCV) is a ubiquitous honeybee virus and a significant pathogen to queen bee ( Apis mellifera ) larvae. However, many aspects of the virus remain poorly understood, including the transmission dynamics. In this study, we used next-generation sequencing to identify BQCV in Aedes vexans ( n = 4, 000) collected in 2019 and 2020 from Manitoba, Canada. We assembled de novo the nearly complete (>96%) genome sequence of the virus, which is the first available from North America and the first report of BQCV being harbored by mosquitoes. Phylogenetic tree reconstructions indicated that the genome had 95.5% sequence similarity to a BQCV isolate from Sweden. Sequences of a potential vector ( Varroa destructor ) and a microsporidian associated with BQCV ( Nosema apis ) were not identified in the mosquito samples, however, we did detect sequences of plant origin. We, therefore, hypothesize that the virus was indirectly acquired by mosquitoes foraging at the same nectar sources as honeybees.